2016
DOI: 10.1039/c6sc00597g
|View full text |Cite
|
Sign up to set email alerts
|

Marcus-type driving force correlations reveal the mechanism of proton-coupled electron transfer for phenols and [Ru(bpy)3]3+ in water at low pH

Abstract: We examined PCET between a series of phenol derivatives and photogenerated [Ru(bpy)3]3+ in low pH (≤4) water using the laser flash-quench technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…emphasizes on MLCT and electronic configuration in excited state . PCET between phenol and [Ru(bpy) 3 ] 2+ at low pH with stepwise electron transfer proton transfer (ETPT) correlating with Marcus type driving force has been reported by Hammarstrom and coworkers . Dempsey et al.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…emphasizes on MLCT and electronic configuration in excited state . PCET between phenol and [Ru(bpy) 3 ] 2+ at low pH with stepwise electron transfer proton transfer (ETPT) correlating with Marcus type driving force has been reported by Hammarstrom and coworkers . Dempsey et al.…”
Section: Introductionmentioning
confidence: 94%
“…[14] PCET between phenol and [Ru(bpy) 3 ] 2 + at low pH with stepwise electron transfer proton transfer (ETPT) correlating with Marcus type driving force has been reported by Hammarstrom and coworkers. [17][18] Dempsey et al have classified the reactants involved in PCET reactions into several categories, one of the category being the excited state proton/electron donors, and have reviewed the recent advances and key discoveries in this area with respect to solar fuel production and small molecule activation. [19] Ruthenium polypyridyl complexes are investigated since the last decade due to their interesting photophysical and electrochemical properties and their potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Based on energetics, molecularity, number of mechanistic steps involved and degree of adiabaticity, PCET processes are classified into different types. 1 , 19 21 Among them, multisite electron proton transfer (MSEPT) is a class where the translocation of an e – /H + pair occurs from a common donor to a different acceptor or from different donors to a common acceptor. 1 Photosystem II is the quintessential example of the MSEPT process, where photo-excited chlorophyll (P 680 + ) acquires an electron (A e ) from tyrosine (D e – /H + ), which decreases its p K a value drastically (p K a = –2) and facilitates the transfer of the proton from tyrosine to the base histidine (A H + ) via the intramolecular hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 The mechanistic details of the electrochemical oxidation of phenol has been well discussed through the Pourbaix diagram by Jean-Michel et al 23 They identified the reaction pathway, where a concerted proton-electron transfer mechanism operated with water acting as a proton acceptor. 21,22 The mechanistic details of the electrochemical oxidation of phenol has been well discussed through the Pourbaix diagram by Jean-Michel et al 23 They identified the reaction pathway, where a concerted proton-electron transfer mechanism operated with water acting as a proton acceptor.…”
Section: Characteristic Redox Behaviour Of Complexes: Evidence For Elmentioning
confidence: 99%